Classics rule the night - New Straits Times, Dennis Chua (2008)
Ther Actors Bangsar presents Classical Twist, a classical music extravaganza featuring three of the finest exponents of the genre in Malaysia. They are acclaimed violinist Joanne Yeoh, planist Dr Lim Pei Sien and cellist Chong Yew Yoong.